Context and Precedent Studies - Jauslin, Daniel (A+BE | Architecture and the Built Environment, 2019)
The first chapter introduces the central questions and purpose of the thesis and explores the ways in which landscape could again become relevant for architecture. I will establish the background to our spatial analysis by defining landscape and architecture in a theoretical elaboration of their crucial interrelations. I will give an outline of the the context of this research (1.1) and state the research questions (1.2). I will open the next section by stating the context of discussion: apparent distinction between architecture and landscape in exemplary theoretical and practical works (1.3). I will then review and reflect on the literature that touched on the subject of this thesis, buildings that have been designed like landscapes, focusing on the aspects that are particularly relevant to the thesis (1.4). These reflections will not only show an increasing interest in landscape as a phenomenon of contemporary architecture but also position the emerging landscape strategies in architecture that I will demonstrate as both critical and urgent towards architects in design practice. Section 1.5. will introduce the methodology in relation to these precedents.